Dialectics of Cultural Dawah and Symbolic Ontology: Transformation of The Mappaleppe Tinja Tradition Towards Tauhid Awareness - Fatimah; Firdaus Muhammad; Mahmuddin; Rahmawati Haruna (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
This study aims to analyze the dialectic between cultural da'wah and symbolic ontology in the transformation of the Bugis community's mappaleppe kaku tradition in Kajuara District, Bone Regency towards monotheistic awareness. This tradition of releasing vows contains theological problems in the form of ontological split-causality when Puang Nene' , offerings, and sacred spaces are interpreted as independent sources of power other than Allah SWT. This existential condition gives rise to tension between the preservation of local culture and the purity of faith. Using qualitative methods with a theological-anthropological approach, data were collected through observation, in-depth interviews, and documentation, then interpreted through theological hermeneutic analysis. The results show that the mappaleppe kaku tradition is a socio-religious construction that binds a sense of collective security through ancestral genealogical memory. Resistance to eliminative da'wah arises due to the strong emotional attachment of the community to this system of meaning, so that confrontational da'wah tends to fail to read the local symbolic structure. As a dialectical solution, this study formulates a mappalettu deceng da'wah model that works through five main stages: mapping religious awareness, stabilizing social relations, contextual theological clarification, reconstructing symbolic meaning, and institutionalizing tawhid awareness. This adaptive-transformative model transmutes the ontological status of material symbols—such as shifting the meaning of offerings from offerings of supernatural powers to horizontal alms ethics—so that the strengthening of tawhid goes hand in hand with the preservation of social cohesion. The novelty of this study lies in the formulation of the mappalettu deceng model as a theological-anthropological meaning management strategy. This model proves that the transformation of tawhid awareness in lived religion is more effective through re-anchoring local symbolic values to His absolute source rather than through frontal cultural elimination.